Efektivitas Permainan Meraih Bintang dan Menggapai Harapan pada Keseimbangan Statis Anak dengan Kondisi Flat Foot - Gyta Krisdiana Cahyaningrum; Naheria Naheria; Sasmiko Sasmiko (CV. AFDIFAL MAJU BERKAH, 2024)
Balance in children plays an important role in maintaining body posture in static and dynamic conditions, regulating and controlling motion stability, and supporting the maturation of motor skills. Motor-related movement disorders in balance and posture are influenced by the impact of flat foot. This research aims to determine the effectiveness the game consists of reaching for stars and achieving hope of the static balance of children with flat foot. The research method used is quantitative with a pre-experimental research group design after testing. The population of this study was the class B group of Samarinda City Kindergarten aged 5-6 years, totaling 60 people. Sampling used a purposive sampling method with the qualifications of respondents who identified the condition of the flat foot as 15 children. The data collection techniques used are observation, experiments, and documents. The data analysis technique used is statistical analysis tif description, Kolmogorov Smirnov normality test, and test paired sample test. Based on the research results, there are significant changes in the abilities of the child's static balance as shown by the results of the paired sample test as big as Sig. (2-tailed) 0.001<0.05, then H0 is rejected and H1 is accepted, meaning that the effectiveness of the game of reaching for stars and achieving hope has a significant influence on children's static balance abilities.